Persepsi petugas puskesmas, kader posyandu, serta akademisi di Kota Yogyakarta terhadap pedoman gizi seimbang (PGS) 2014 - Risma Saski Rahmita; Yayi Suryo Prabandari; Siti Helmyati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2016)
ABSTRACTBackground: Based on the Basic Health Research on 2013, Indonesia is currently experiencing the global burden diseases. The prevalence of nutritional problems is higher than the limit of nutritional problems in the community, e.g. stunting 37.2 %, underweight 19.6%, and overweight 11.9%. This situation is quite alarming for the quality of Indonesian human resources. Therefore, guidelines for balanced nutrition that consists of 10 nutrition messages become important to solve. To know the readability of the guidelines in community, the perception of health center officers, cadres of posyandu, and academics to guidelines are needed.Objectives: To explore the perception of health center officers, cadres of posyandu, and academics to guidelines for balanced nutrition 2014.Methods: This research was a qualitative-based research with focus group discussions (FGD) methods. There were three different groups conducted in this research, e.g. health center officers, cadres of posyandu, and academics.Results: There were some unclear messages to all groups, such as the words “many” and “enough” in the second message, “high protein” in the 3rd message, “safe” and “enough” in the 7th message, and “physical activity” in the 10th message. From the picture of nutrition guidelines (nutrition pyramid), there was incompatibility between the nutrition pyramid and the guidelines for balanced nutrition 2014, especially in portions and the size of picture.Conclusions: Guidelines for balanced nutrition 2014 had of been different percepted especially nutrition messages and the pyramid.KEYWORDS: perception, guidelines for balanced nutrition 2014, nutrition pyramidABSTRAKLatar belakang: Berdasarkan riset kesehatan dasar (Riskesdas) 2013, Indonesia saat ini mengalami beban ganda masalah gizi. Prevalensi masalah gizi yang ada masih melebihi batas masalah gizi masyarakat: gizi kurang dan pendek 37,2%, gizi kurang 19,6%, dan gizi lebih 11,9%. Keadaan ini cukup mengkhawatirkan bagi kualitas sumber daya manusia Indonesia. Oleh karena itu, diperlukan adanya upaya untuk memperbaiki keadaan ini dengan wujud mengeluarkan pedoman gizi seimbang (PGS) yang terdiri dari 10 pesan gizi yang telah disesuaikan oleh perkembangan permasalahan gizi di masyarakat. Untuk melihat keterbacaan pedoman gizi seimbang ini di masyarakat, perlu dilihat persepsi petugas puskesmas, kader posyandu, serta akademisi terhadap PGS 2014.Tujuan: Mengeksplorasi persepsi petugas puskesmas, kader posyandu, serta akademisi terhadap PGS 2014.Metode: Penelitian ini merupakan penelitian kualitatif dengan metode diskusi kelompok terarah (DKT) terhadap tiga kelompok berbeda, yaitu petugas puskesmas, kader posyandu, juga akademisi.Hasil: Secara keseluruhan ada beberapa poin pesan yang dirasa kurang jelas untuk semua kelompok, seperti kata-kata “banyak” dan “cukup” pada pesan 2, “protein tinggi” pada pesan 3, “aman” dan “cukup” pada pesan 7, dan “aktivitas fisik” pada pesan 10. Untuk gambar pada tumpeng gizi seimbang (TGS), adaketidaksesuaian antara tumpeng dengan PGS 2014, khususnya pada porsi dan ukuran gambarnya.Kesimpulan: Sejauh ini, PGS 2014 masih memunculkan beragam persepsi terkait poin-poin pesan dan juga gambarnya.KATA KUNCI: persepsi, pesan gizi seimbang (PGS) 2014, tumpeng gizi seimbang (TGS) 2014